Climbing ability of ducklings of some cavity-nesting waterfowl - Siegfried, W Roy (Wildfowl, 1974)
The tendency and ability of newly hatched ducklings to climb out of an experimental chimney were examined in the following species: American Wood Duck Aix sponsa. Mandarin Aix galericulata, American Goldeneye Bucephala clangula, Hooded Merganser Mergus cucullatus and Mallard Anas platyrhynchos. The Wood Duck performed consistently best. In climbing up a vertical surface, the Wood Duckling proceeds by a series of leaps and uses its tail as a brace, rather like a Woodpecker. The Wood Duckling has relatively short legs, strongly decurved toe-claws, and long and broad caudal down shafts. The importance of stimuli prompting the young of cavity-nesting waterfowl to leave the nest, is discussed.